2016
DOI: 10.7554/elife.12792
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha somatic mutations Y537S and D538G confer breast cancer endocrine resistance by stabilizing the activating function-2 binding conformation

Abstract: Somatic mutations in the estrogen receptor alpha (ERα) gene (ESR1), especially Y537S and D538G, have been linked to acquired resistance to endocrine therapies. Cell-based studies demonstrated that these mutants confer ERα constitutive activity and antiestrogen resistance and suggest that ligand-binding domain dysfunction leads to endocrine therapy resistance. Here, we integrate biophysical and structural biology data to reveal how these mutations lead to a constitutively active and antiestrogen-resistant ERα. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
266
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(282 citation statements)
references
References 51 publications
(82 reference statements)
14
266
0
2
Order By: Relevance
“…S7A). These values are in agreement with a recent study [24] but are significantly lower than values published in previous studies [14,25], likely due to differences in experimental design. Based on the precise determination of the affinity for estradiol, we determined that the K i value for non-covalent H3B-9224 was 2-fold higher than 4-OHT for ER WT and ER Y537S ( Supplementary Fig.…”
Section: H3b-5942 Is Dependent On Covalent Engagement For Enhanced Ersupporting
confidence: 70%
See 1 more Smart Citation
“…S7A). These values are in agreement with a recent study [24] but are significantly lower than values published in previous studies [14,25], likely due to differences in experimental design. Based on the precise determination of the affinity for estradiol, we determined that the K i value for non-covalent H3B-9224 was 2-fold higher than 4-OHT for ER WT and ER Y537S ( Supplementary Fig.…”
Section: H3b-5942 Is Dependent On Covalent Engagement For Enhanced Ersupporting
confidence: 70%
“…Mechanistically, the Y537 and D538 mutations are located in the AF-2 helix of ER and introduce a stabilizing interaction to shift the dynamic equilibrium towards the agonist conformation even in the absence of ligand [14,15]. We reasoned that for a compound to be more active in the mutant setting, it would necessarily have to overcome the stabilizing effects of the mutation and shift the equilibrium towards the destabilized antagonist conformation.…”
Section: Identification Of H3b-5942mentioning
confidence: 99%
“…This was shown in vitro as well as in vivo using breast cancer cell lines engineered to express the mutations and PDXs derived from human metastatic breast cancer tumors harboring the LBD mutations [10,11,14]. The crystal structure and simulation studies of tamoxifen bound to the D538G and Y537S mutants indicate that the ER LBD mutations lead to decreased affinity to tamoxifen and confer an altered antagonistic conformation facilitating resistance to antagonism by tamoxifen [17]. Fulvestrant also binds to the LBD; however, the structure of the mutant LBD bound to fulvestrant has not been resolved.…”
Section: Esr1 Mutations and Endocrine Therapymentioning
confidence: 99%
“…Conversely, antagonist binding to the LBD induces an inactive conformation of H12 that promotes co-repressor binding and inhibition of the receptor activity. The Y537S and D538G ER mutations stabilize H12 in the agonistic conformation, similar to WT-ER bound to E2 [16,17]. In addition, affinity studies showed that the LBD-mutated receptors have a decreased affinity for estradiol (E2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation